DETERMINAN PEMILIHAN MODA TRANSPORTASI PEKERJA KOMUTER JABODEBATEK DENGAN MODEL REGRESI LOGISTIK MULTINOMIAL MULTILEVEL - Hernanto Adwiluvito; Indonesian Journal of Statistics; Its Applications IJSA (Statistics and Data Science Program Study, SSMI, IPB University, in collaboration with the Forum Pendidikan Tinggi Statistika Indonesia (FORSTAT) and the Ikatan Statistisi Indonesia (ISI), 2019)
The BPS noted that commuters in Jabodetabek had increased by 400 thousand people from 2001 to 2014. The BPS also recorded that around 81,3% of the commuters in Jabodetabek were workers. A growing number of commuter workers in Jabodetabek makes transportation is very important to support the connection of suburban area and workplace in Jakarta. The result showed that 73% of the commuter workers used private transportation, 19% used ground public transportation and the rest of commuter workers used train. This research use Jabodetabek Commuter Survey 2014 as the main source data to shed light on how socioeconomic factors and spatial attributes affect the selection of a primary mode of transportation for commuter workers. Using multilevel multinomial logistic regression, the result confirm that the age, sex, marital status, ownership of vehicle, travel distance and time have a significant effect in explaining train choice. Furthermore, the result also showed that the age, sex, marital status, income, ownership of vehicle, travel distance and cost are found to be significant in explaining ground public transportation choice.